Hermeneutika Politik Dalam Literasi Pendidikan Demokrasi Pancasila (Studi Deskriptif Tahun Pemilu dan Pilkada 2024 di Indonesia) - Yohanes Probo Sasongko; Erwin Setyawan (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2023)
Our knowledge and understanding of political diction still needs further attention. This is in line with efforts to provide good education to society. Looking ahead to the political year 2024, Indonesian people are still trapped by limitations and inadequate understanding of the meaning of politics. The impacts felt are also varied, starting from acts of discrimination, intolerance and attitudes of exclusivism towards groups and groups within themselves. Political hermeneutics tries to look again at the understanding and definition of politics openly and comprehensively, meaning that in the context of hermeneutic studies, diction regarding politics is brought back to a different understanding and is able to look at a comprehensive context. So, in this new understanding, the Indonesian people can prepare themselves and be fully aware to be actively involved, and able to play an open role in assisting and assisting our neighbors as a nation that prioritizes the values of Pancasila to become a good and advanced Indonesian nation. Our nation is heading towards a Golden Indonesia 2045.